A study of buckling analyses of piping structures. (May 2019) - Wiseman, Phillip E.; Barkey, Mark E.
Abstract: The pipe support and restraint design by analysis buckling criteria for linear and plate-and-shell-type (P&S) supports given within the American Society of Mechanical Engineers (ASME) Boiler and Pressure Vessel Code, Section III, Division 1, Subsection NF is investigated to determine if it should be refined to include a basis upon instability criterion. If a Class 1 support is considered linear-type or plate-and-shell-type (P&S), the allowable buckling load is limited to two-thirds or one-half of the calculated critical buckling load, respectively. Five types of analyses are performed to demonstrate finite element and closed form solutions including linear Euler method, nonlinear second order large deformation method, nonlinear large deformation method with nonlinear elastic-plastic material, energy method, and Euler-Bernoulli beam theory. The techniques are compared with explanations of the considerations taken and their impact on the final solution. The structural components chosen to conduct the buckling analyses are rigid struts which are an integral part of commercial nuclear power plants. Highlights: Nonlinear buckling analysis solutions should be obtained to get a better idea of real-world conditions and scenarios. Elastic buckling is a mode of failure that should not be defined by yield criterion. The critical buckling factor for plate-and-shell-type supports should be increased to 2/3 for Level B & C in ASME B&PV Code.